Asuhan keperawatan keluarga pada pasien Gout arthritis dengan masalah nyeri - Novita, Sri; Resmi, Resmi Pangaribuan; Khairani, Ade Irma (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Gout arthritis is a joint inflammation caused by the accumulation of uric acid crystals in the joints. Family involvement in patient care is crucial for reducing pain complaints and evaluating the effectiveness of warm compress therapy in reducing pain. This research method uses a descriptive case study method with a family nursing care approach including assessment, nursing diagnosis, intervention, implementation, and evaluation. The inclusion criteria for this study were willingness to be respondents, family members with a medical diagnosis of gout arthritis and a nursing diagnosis of pain, age >45 years, male or female. The study was conducted at the Pulo Brayan Community Health Center for 1 week with 3 meetings. The instruments used were a family nursing assessment sheet, an observation sheet, and a warm compress SOP. The results of this study in both responses stated a decrease in pain in the affected limb, the first patient said a scale of 5 to 2, and the second patient from a scale of 6 to 3. Analysis of the research results showed that warm compresses were effective in reducing pain and required a family role in the care of gout arthritis patients. In conclusion and recommendations, active family involvement and routine non-pharmacological interventions are effective in reducing patient pain levels and increasing comfort during home care. Suggestions for families are expected to encourage them to play an active role in caring for family members with gouty arthritis.